Eseistyka Wojciecha Gniatczyńskiego odkrywana (na nowo?). Przyczynek do badań - Zahaczewska, Izabela (Tematy i Konteksty, 2018)
The article presents the profile of one of the forgotten and underestimated writers of Polish emigration after 1939 – Wojciech Gniatczyński. The intricate history of his life is the story of a man marked by the stigma of war and the traumatic experiences of a concentration camp, and an emigrant with unfulfilled ambitions, who disappeared into the shadows of his more combatived colleagues. Discussed briefly essay writing of Gniatczyński shows him unusual erudition and a writing workshop with great artistic, aesthetic and cognitive qualities. It gives the possibility of various interpretations and urges to multifaceted research, clearly indicating that Wojciech Gniatczyński is worth rediscover today.